2022
DOI: 10.1111/ijac.14176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser parameters and atmosphere in the structuring of aluminum nitride

Abstract: The characteristics and formation mechanism of V-shaped groove formed by laser-activated metallization of aluminum nitride (AlN) ceramic under different shielding gas environments of air, nitrogen, and argon are investigated, using a novel analysis way which is based on the intensity distribution of the focused laser beam. It is found that the width of the V-shaped groove is slightly different under different gas environments, and the depth of the V-shaped groove is nearly the same, which means that the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…While coatings have been implemented in earlier research to reduce or completely inhibit the bulk reactivity of AlN substrates, [38][39][40] varying laser processing parameters were em-ployed here to ensure coverage of the substrate by a layer of aluminum oxides (as shown earlier in Figure 1B), which would inhibit any tendency of the working liquid (herein water) to react with the bulk AlN substrates. [43,50,51] To further demonstrate the effectiveness of the laser ablation process in preventing surface degradation via hydrolysis, and show that wettability patterns are unaffected at high temperatures during phase change heat transfer, a simple experiment was performed (Section S2.1, Supporting Information; Confirming surface degradation resistance). The experimental results showed no appreciable change in the physicochemical properties of either the hydrophilic or hydrophobic domains on the AlN sample.…”
Section: Aln Surface Passivation and Wettability Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…While coatings have been implemented in earlier research to reduce or completely inhibit the bulk reactivity of AlN substrates, [38][39][40] varying laser processing parameters were em-ployed here to ensure coverage of the substrate by a layer of aluminum oxides (as shown earlier in Figure 1B), which would inhibit any tendency of the working liquid (herein water) to react with the bulk AlN substrates. [43,50,51] To further demonstrate the effectiveness of the laser ablation process in preventing surface degradation via hydrolysis, and show that wettability patterns are unaffected at high temperatures during phase change heat transfer, a simple experiment was performed (Section S2.1, Supporting Information; Confirming surface degradation resistance). The experimental results showed no appreciable change in the physicochemical properties of either the hydrophilic or hydrophobic domains on the AlN sample.…”
Section: Aln Surface Passivation and Wettability Modificationmentioning
confidence: 99%
“…Laser processing of the AlN substrates resulted in surface passivation with varying roughness and surface coverage, as demonstrated in Figure 2A (for an individual surface profile of each sample refer to Section S2 (Supporting Information): Laser-induced AlN surface passivation). Overlap of the laser scans [43] was kept high (≈90%) to ensure complete coverage, the power input varied Varying laser parameters resulted in different roughness features. B) To evaluate the liquid-wicking ability of each surface, water droplets (4.87 μL) were dispensed one-at-a-time on 2 × 2 cm samples (second row) and visualized using a high-speed camera.…”
Section: Aln Surface Passivation and Wettability Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…5,42 To make nitrogen better incorporated into the material, in some cases, the nitrogen gas could also be sprayed to the heated site by a jet. 43 Katayama et al 44 technique for enhancing the titanium surface mechanical properties for the first time. Since then, the LN technique has been used to treat a variety of alloys and metals, such as aluminum, stainless steel, iron, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that laser surface modification of metals can enhance their hardness, fatigue strength, and wear resistance. As a neoteric method, laser nitriding combines the advantages of surface nitriding and laser modification. In a laser nitriding process, a laser beam locally focuses on the metals to heat the surfaces in a nitrogen atmosphere. , To make nitrogen better incorporated into the material, in some cases, the nitrogen gas could also be sprayed to the heated site by a jet . Katayama et al reported an LN technique for enhancing the titanium surface mechanical properties for the first time.…”
Section: Introductionmentioning
confidence: 99%